The impact of the Nitaqat programme on the Saudi labour market - Bagazi, Tahani (2020)
This research evaluates Saudi Arabia's Nitaqat quota policy within a labour market context, where the target group (Saudis) is earning double the pay of the untargeted (non-Saudis) group1. We aim to examine the wage gap between the two groups to address its sources and discover how the quota can change this gap. This allows an understanding of how the quota affects Saudis' welfare. Moreover, understanding the gap in firm status allows an evaluation of the layoff risks, firms' employment behaviours and the earning structure changes. The Oaxaca–Blinder decomposition, a standard econometrics tool, is used empirically. This methodology is based on estimates from the ordinary least squares method. Data for two years, 2013 and 2017, was available, and a pooled sample for the two years was used. We find that the gap could be explained by around 34% in 2013 and 71% in 2017, while the remaining gap was due to the differences in earnings structures between the groups, especially the starting wages. The remainder of the gap was unexplained by a high percentage due to the different wage structures, especially the starting wage (via intercept), which implies that unknown variables could explain the gap. However, the explained percentage jumped to 80% and 85%, respectively, when we included consumption as a new exploratory variable. Additionally, we found heterogeneity in the wage gap among workers' origins. This implies that the gap could be closed if we considered some other unobserved variable, such as the wages in the sending countries. Additionally, the wage gap between workers in localised and non-localised firms was in favour of workers in localised firms in both years. Furthermore, workers responded to the Nitaqat quota in the opposite direction of that predicted by the hedonic wage model when layoff risks existed, but they were consistent with this wage model when unemployment benefits were imposed. Accordingly, non-Saudis in non-localised firms could be described as a double negative group. Moreover, the gap narrowed between the groups because Saudis' wages decreased twice as much as non-Saudis' wages. This resulted from a massive redistribution of Saudi workers towards the quota minimum wage, which coincided with a reduction in education returns. In other words, linking the policy with a specific wage allowed firms to replace qualified Saudis with unqualified Saudis rather than Saudis with non-Saudis. Thus, firms balanced their costs by offering low-quality jobs for Saudis, aiming to achieve reasonable profits. We conclude that the Nitaqat quota policy negatively impacted Saudis' wages; however, it achieved some of its aims, such as decreasing the gap and controlling the unemployment rate. This resulted from the responses of firms and workers towards the policy; the policy lost its power because of the redistribution of firms' sizes and the redistribution of workers among occupations. An effective gap decrease requires the policy to make distinctions between occupations to ensure the job quality is provided. Moreover, adding some criteria or fees to Nitaqat could shift the replacements among non-Saudis, taking the substituted relationship and the labour intensiveness into consideration.
HydraID: hull:18339 Hydra Discover Access Group: public ETD Collection: ETDBusinessSchool
Keywords: Business